(untitled) (Movimenta (ISSN 1984-4298), 2018)
The production of scientifical and technological knowledge is very important for the development of society, as well as for the qualitative advancement of all the professions. Physiotherapy is an area with great expansion and, the dissemination of its productions in the scientific community, may cause great advancement for the professional itself and for the health studies. The aim of this study was to analyze the scientific production (fully available papers) published by the professors of the course of Physiotherapy of the State University of Goias (SUG), between the period of 2000 and 2008 years. Under a longitudinal retrospective design study, the articles published by each professor were collected by mean of their respective Curriculum Vitae Lattes. The technical quality of the papers was verified by the Qualis score of each published periodical on the “Physical Education, Phisical Therapy and Occupational Therapy” area. With respect to the data analysis, we applied the descriptive statistics (average and standard deviation) as well as the tStudent parametric test for pared sample, with a 5% level of significance. The results had showed a significative increase of the scientific production considering the period of 2000-2008. Nevertheless, there was an unexpressive average of 0.056 articles/professor/year. Regarding the Qualis score, it was noticed articles published on world-wild know periodicals were minority. In conclusion, the scientific increased of published papers is very important for the Institution. Nevertheless, the State University of Goias needs to improve itself to become a reference center of studies.